(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
The article analyzes the development trends of the stock market at the national and international level, the current state of operations in the stock market, and determines the factors influencing the development of the stock market. The stock market is an important tool for economic growth, as it is able to transform savings into investments. Therefore, in the context of globalization, the study of the conditions for the formation and development trends of the stock market is relevant.Objectives. Assessment of the current state of the stock market, identification of key problems hindering its effective development, and development of measures to eliminate them. Methodology. Used logical, statistical and graphical methods of analysis. Results. Problems that impede the effective development of the stock market are identified. First of all, it is the low level of capitalization of the stock market, the lack of developed infrastructure, failure to establish an effective mechanism for issuing and selling securities, the abundance and complexity of legal documents related to the stock market sector and the existence of many restrictions, insufficient improvement of the mechanism of protection of investors’ interests and absence of institutional investors and professional market participants. Concrete proposals have been formulated to eliminate the problems of the development of the stock market: attracting domestic and foreign investors, increasing the dividend yield on shares by issuers, improving the legal framework and taxation system, developing a system for insuring transactions in the stock market, and implementing the principle of information openness. Conclusions. Further development of the stock market is possible only with an integrated approach both on the part of the market itself and the state. In order to attract new investors to the domestic stock exchange, it is necessary to regularly carry out activities to improve the financial literacy of the population and develop new tools to involve citizens in investing.